Occupational Hazards in Firefighting: Systematic Literature Review - María F. Cuenca-Lozano; César O. Ramírez-García (Elsevier, 2023)
Background: Firefighting involves exposure of firefighters to risks related to this activity, serious injuries, and occupational diseases are recorded. There are other consequences such as thermal and emotional stress. This systematic review is proposed in order to analyze the risks and consequences faced by these workers and thus provide elements to improve safety management systems in institutions. Method: A descriptive observational study of systematic literature review on the risks and consequences of exposure to firefighters' activity was proposed, and the information was analyzed and described based on the available data and according to the variables determined. Results: The studies showed data on mechanical, physical, chemical, psychosocial risks, workers' perception and resilience, and epidemiological data. Information related to firefighters' activity on falls and slips, exposure to noise, and high concentrations of carbon monoxide is detailed. In addition, the relationship between burnout, cognitive, and physical fatigue as adverse effects on health and performance is mentioned. Conclusions: Among the preventive measures, the use of personal protective equipment is suggested, incorporation in prevention programs of information on exposure to risk factors, as well as the implementation of models that can predict the perception of workers, additionally, the generation of management systems with safety climate models for fire departments.